Seismic performance of flexure-dominated reinforced-engineered cementitious composites coupled shear wall. (1st December 2022) - Ye, Binbin; Wang, Haishen; Ma, Yuhong; Pan, Peng
Highlights: Reinforced-ECC (RECC) coupling shear walls were cyclic loaded until failure. The RECC coupling shear wall exhibited smeared cracking characteristics with a significantly smaller crack width. The deformation capacity of the RECC coupling shear wall was twice that of the RC counterparts. The feasibility of using ECC to improve the seismic performance of coupling shear walls was preliminary verified. Abstract: The feasibility of using engineered cementitious composites (ECC) to improve the seismic performance of coupled shear walls was investigated experimentally and analytically. Reinforced-ECC (RECC) coupled shear wall was tested under cyclic loading for comparative study with its RC counterparts. Important seismic performance indicators, such as the deformation mode, damage pattern, stiffness, ductility and energy dissipation of the two coupled shear walls were compared and analyzed. The RECC shear walls and RC shear walls exhibited flexural failure modes with different damage patterns. The damage was concentrated mainly in the plastic hinge area, which include the bottom of the wall and the ends of the coupling beams. The RECC shear wall exhibited smeared cracking characteristics with a significantly smaller crack width. The RECC members showed ductile failure mode without crushing or spalling, and provided effective restraint to the longitudinal rebar, which delayed the buckling of the longitudinal rebar. The deformation capacity of the RECC shear wall was twice that of the RC shear wall, and the energy dissipation capacity of RECC shear wall also improved significantly compare to RC shear wall. The RECC shear wall exhibited a slightly higher load-bearing capacity compared with its RC counterpart. The ultimate strength of the RECC and RC coupled shear walls were estimated based on the compression–bending mechanism. The calculated results agreed well with the test results. The estimated yield and ultimate displacement of the RECC and RC shear walls were close to the test results.